Managing bank capital : capital allocation and performance measurement - Matten, Chris (John Wiley & Sons, 2000)
Managing Bank Capital explains proven techniques available in the management of bank capital that will help maximize shareholder value. This second edition has been fully updated to incorporate significant developments, such as the modeling of credit risk, and includes new sections with more technical information and advanced analysis.